Bibliometric analysis: The reputation of Indonesian law enforcement officials on social media - Valentina, Indira Restu; Permana, Iip (Privietlab, 2025)
Law enforcement plays a crucial role in maintaining public safety and welfare, making the reputation of law enforcement agencies a key concern, particularly in the digital space. This study maps the research landscape of the reputation of law enforcement organizations on social media through a bibliometric approach. Data was collected from Google Scholar using Publish or Perish (keywords: